AN OPPORTUNITY TO DEVELOP HALAL FASHION INDUSTRY IN INDONESIA THROUGH E-COMMERCE PLATFORM - Novalini Jailani; Kuat Ismanto; Susminingsih; Hendri Hermawan Adinugraha (Tadayun: Jurnal Hukum Ekonomi Syariah, 2022)
Nowadays, fashion has become a global business. Indonesian Muslim consumption in the Halal Fashion sector in 2021 reached 20 billion USD. Moreover, knowing that the Indonesian population was also dominated by millennials and Gen Z, reaching 144.31 million people or 53.81% of the total population, this generation is familiar with and masters technology. The halal fashion industry can utilize this condition to develop its business through e-commerce platforms. Therefore, this study aims to explore and explain the development opportunities of the halal fashion industry in Indonesia through e-commerce platforms. This research was conducted by literature research with a descriptive qualitative approach. Secondary data were obtained from various books, articles, journals, reports, and authoritative websites relevant to this research. The results of this study found that the economic potential of the halal fashion industry sector in Indonesia is very promising. That can be seen from the consumption of Muslims in Indonesia for halal fashion, which continues to increase yearly. Indonesia's demographic bonus, dominated by millennials and Gen Z who are familiar with technology, and the increasing number of E-Commerce users in Indonesia provide an excellent opportunity for this industry to develop further. Abstrak Saat ini fashion telah menjadi bisnis global. Konsumsi Muslim Indonesia di sektor Halal Fashion pada tahun 2021 akan mencapai 20 miliar USD. Apalagi mengetahui fakta bahwa penduduk Indonesia juga didominasi oleh kaum milenial dan Gen Z yang jumlahnya mencapai 144,31 juta jiwa atau 53,81% dari total populasi, generasi ini sangat akrab dan menguasai teknologi. Kondisi ini dapat dimanfaatkan oleh industri fashion halal untuk mengembangkan bisnisnya melalui platform e-commerce. Oleh karena itu, penelitian ini bertujuan untuk menggali dan mendeskripsikan peluang pengembangan industri halal fashion di Indonesia melalui platform e-commerce. Penelitian ini dilakukan dengan penelitian kepustakaan dengan pendekatan kualitatif deskriptif. Data sekunder diperoleh dari berbagai buku, artikel, jurnal, laporan dan website otoritatif yang relevan dengan penelitian ini. Hasil penelitian ini menemukan bahwa potensi ekonomi pada sektor industri halal fashion di Indonesia sangat menjanjikan. Hal ini terlihat dari konsumsi muslim di Indonesia terhadap halal fashion yang terus meningkat dari tahun ke tahun. Bonus demografi Indonesia yang didominasi oleh kaum milenial dan gen Z yang akrab dengan teknologi serta meningkatnya pengguna E-Commerce di Indonesia memberikan peluang besar bagi industri ini untuk berkembang lebih jauh lagi.